Adaptation and application of the SERVQUAL scale in higher education - Oliveira, Otávio J.; Ferreira, Euriane Cristina (Revista Gestão da Produção Operações e Sistemas, 2008)
Higher education in developing countries has serious quality problems. In order to change this scenario, it is necessary to invest in quality systems and tools for improvement. The SERVQUAL scale is one of these alternatives. It is used to measure the gap between quality expectations and perceptions in services making it possible to establish action plans. The objective of this paper is to propose an adaptation of the SERVQUAL scales generic questionnaire for the higher education service sector and present the main results of its application in students of the production engineering program at São Paulo State University (UNESP) in Brazil. Thirty-eight questionnaires were applied to measure perception in entering students and twenty-eight to measure expectations in graduating students. Key words: SERVQUAL, quality management, service management, higher education.